THE EFFECT OF MANAGEMENT CHANGE, AUDIT OPINION, COMPANY SIZE, FINANCIAL DISTRESS AND AUDITOR REPUTATION ON AUDITOR SWITCHING - Ahmad Zakie Mubarrok; Almer Reyhan Islam (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2020)
This study aims to empirically prove the effect of management change, audit opinion, company size, financial distress and auditor reputation on auditor switching. This research was conducted on manufacturing companies that have been listed in Indonesian Stock Exchange from 2016 – 2018. There were 109 companies collected for observation in which they were taken by the method of purposive sampling. An analytical technique employed is logistic regression analysis. The results of hypothesis testing in this research indicate that management change, audit opinion, financial distress and auditor reputation affects the auditor switching. Meanwhile variabel of company size affect auditor switching, but in positive effect